In search of miracles. Issue 3 (2nd September 2018) - Stjerna, Kirsi
Abstract: The movie The Third Miracle invites theological reflection on miracles, sainthood, and faith. A movie filled with Lutheran themes of unmerited grace and blessings of the ordinary life, the story line follows a Catholic priest tasked with exploring the authenticity of reported miracles associated with a lay woman and a bleeding statue. Faith and miracles are shown in their ordinariness, easily missed without the eye of faith, and sainthood is juxtaposed with the expected and unexpected vis‐à‐vis motherhood.